2009
DOI: 10.1681/asn.2008070730
|View full text |Cite
|
Sign up to set email alerts
|

Combining GFR and Albuminuria to Classify CKD Improves Prediction of ESRD

Abstract: Despite the high prevalence of chronic kidney disease (CKD), relatively few individuals with CKD progress to ESRD. A better understanding of the risk factors for progression could improve the classification system of CKD and strategies for screening. We analyzed data from 65,589 adults who participated in the Nord-Trøndelag Health (HUNT 2) Study (1995 to 1997) and found 124 patients who progressed to ESRD after 10.3 yr of follow-up. In multivariable survival analysis, estimated GFR (eGFR) and albuminuria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
299
1
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(323 citation statements)
references
References 37 publications
12
299
1
11
Order By: Relevance
“…As shown in the present study, proteinuria and age contributed differently to CKD outcomes. Proteinuria and albuminuria are accepted markers of kidney damage, and are associated with lower eGFR and an increased risk of subsequent ESRD (31)(32)(33)(34)(35)(36)(37)(38)(39). On the other hand, age is inversely associated with ESRD and positively associated with death (7,40 -43).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the present study, proteinuria and age contributed differently to CKD outcomes. Proteinuria and albuminuria are accepted markers of kidney damage, and are associated with lower eGFR and an increased risk of subsequent ESRD (31)(32)(33)(34)(35)(36)(37)(38)(39). On the other hand, age is inversely associated with ESRD and positively associated with death (7,40 -43).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Matsushita et al 5 observed an increased risk for CVD and all-cause mortality from RKFD in those with eGFR 60 to 90 ml/min per 1.73 m 2 at baseline, and other studies of the general population show an increased risk for adverse outcomes from RKFD or proteinuria independently of baseline eGFR. 4,6,13,14 Although albuminuria has greater sensitivity at low levels and is the recommended method for monitoring proteinuria in diabetics, [15][16][17] we show that dipstick urinalysis, an inexpensive test that is already a common feature of primary care, has better diagnostic utility for identifying RKFD.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the meaning of RKFD at eGFR Ͼ90 ml/min per 1.73 m 2 is less clear because there is no body of evidence documenting adverse outcomes in this group. 19 Although previous research has established that proteinuria in the presence of eGFR Ͻ60 ml/min per 1.73 m 2 is a stronger risk factor for CVD and ESRD than either indicator alone, 13,20 serial eGFR assessment would provide additional information about a patient's risk trajectory. For example, in elderly patients with reduced but stable kidney function, a low eGFR (30 to 60 ml/min per 1.73 m 2 ) may be an indicator of age-related comorbidity rather than vascular pathology, the latter being responsive to treatment with angiotensin-receptor blockers if caused by proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is common in diabetes patients with nephropathy, and its severity worsens with more advanced stage of CKD and proteinuria2. At the same time, low estimated glomerular filtration rate (eGFR) and high urine albumin are two major risk factors for ESRD with strong predictive powers15. More proof is still awaited on the relationships among anemia, nephropathy and progression of renal disease.…”
Section: Introductionmentioning
confidence: 99%